2015
DOI: 10.1016/j.ins.2015.02.018
|View full text |Cite
|
Sign up to set email alerts
|

A chi-square method for priority derivation in group decision making with incomplete reciprocal preference relations

Abstract: a b s t r a c tThis paper proposes a chi-square method (CSM) to obtain a priority vector for group decision making (GDM) problems where decision-makers' (DMs') assessment on alternatives is furnished as incomplete reciprocal preference relations with missing values. Relevant theorems and an iterative algorithm about CSM are proposed. Saaty's consistency ratio concept is adapted to judge whether an incomplete reciprocal preference relation provided by a DM is of acceptable consistency. If its consistency is una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…. w n ) T is able to precisely fit the reciprocal preference relation C (k) , then |d Table 2, it's shown that the LDM achieves an identical ranking as LSM [14], CSM [37], and LLSM [44], while the ranking derived by GPM [47] is slightly different. The GPM fails to discriminate x 2 and x 4 .…”
Section: Examplementioning
confidence: 96%
See 1 more Smart Citation
“…. w n ) T is able to precisely fit the reciprocal preference relation C (k) , then |d Table 2, it's shown that the LDM achieves an identical ranking as LSM [14], CSM [37], and LLSM [44], while the ranking derived by GPM [47] is slightly different. The GPM fails to discriminate x 2 and x 4 .…”
Section: Examplementioning
confidence: 96%
“…For this single incomplete reciprocal preference relation, it can also be solved by the EM [46], NRAM [38], LSM [14], LLSM [44], CSM [37] and GPM [47]. The results are shown in Table 5, from which we can see that LDM achieves the same ranking x 2 x 4 x 5 x 3 x 6 x 1 as LLSM, GPM, NRAM and CSM.…”
Section: Examplementioning
confidence: 97%
“…In Example 1, Zhang 16 obtained the multiplicative consistent HFPR, in which the element mh 23 = {0.3132, 0.3184, 0.2949}. It is obvious that the values in mh 23 are not arranged in ascending order, which is inconsistent with his definition. But if the value of mh 23 is arranged in ascending order, mH is not a multiplicative consistent HFPR according his definition.…”
Section: A Case Of Studymentioning
confidence: 97%
“…(9) In mH,mh 23 = {0.3132, 0.3184, 0.2949}, its elements do not arrange in ascending order, because 0.2949 is smaller than 0.3132 or 0.3184, which do not meet the requirement h…”
Section: Hesitant Fuzzy Preference Relations (Hfprs)mentioning
confidence: 99%
See 1 more Smart Citation